2012
DOI: 10.1029/2011ja016913
|View full text |Cite
|
Sign up to set email alerts
|

Chorus intensification in response to interplanetary shock

Abstract: , the Time History of Events and Macroscale Interactions during Substorms (THEMIS) satellites observed a significant intensification of chorus in response to the interplanetary shock in the Earth's dayside plasma trough. We analyze the wave-particle interaction and reveal that the chorus intensification can be caused by the gyroresonance between the chorus and the energetic electrons. When the electrons are scattered from resonance points to low-density regions along the diffusion curves, a part of their energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 88 publications
4
88
1
Order By: Relevance
“…3. the electron distribution measured by MMS 2 and 3, in the magnetosheath-side inflow region with nullspacecraft distance of 20 or 30 km (2-D distance; see Figure 3m), is cigar-type (T // > T ⊥ ) at low-energy channels but exhibits a loss feature in the antiparallel direction at high-energy channels (Figures 3f and 3g and 3j and 3k). This scenario is somewhat similar to that in the radiation belt, where quasi-perpendicular electrons have mirror points close to the magnetic equator and the ionospheric collision leads to the loss cone distribution (Fu et al, 2011(Fu et al, , 2012. In this way, these quasiperpendicular electrons (population B and C) will be stably trapped in the inflow region and get energized via the Fermi process during the multiple bounces between the mirror points, as the case measured by MMS 4 in the magnetosphere-side inflow region.…”
Section: Electron Distribution Functions Around the X-linesupporting
confidence: 54%
“…3. the electron distribution measured by MMS 2 and 3, in the magnetosheath-side inflow region with nullspacecraft distance of 20 or 30 km (2-D distance; see Figure 3m), is cigar-type (T // > T ⊥ ) at low-energy channels but exhibits a loss feature in the antiparallel direction at high-energy channels (Figures 3f and 3g and 3j and 3k). This scenario is somewhat similar to that in the radiation belt, where quasi-perpendicular electrons have mirror points close to the magnetic equator and the ionospheric collision leads to the loss cone distribution (Fu et al, 2011(Fu et al, , 2012. In this way, these quasiperpendicular electrons (population B and C) will be stably trapped in the inflow region and get energized via the Fermi process during the multiple bounces between the mirror points, as the case measured by MMS 4 in the magnetosphere-side inflow region.…”
Section: Electron Distribution Functions Around the X-linesupporting
confidence: 54%
“…These waves frequently exhibit a two-band structure with a power minimum near 0.5f ce0 (Burtis & Helliwell, 1976;H. Usually observed outside the plasmapause, chorus waves consist of narrow band discrete emissions with frequency chirping due to nonlinear wave-particle interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Dayside whistler mode chorus is at times related to sudden enhancements of the solar wind dynamic pressure. It has been reported that a sudden magnetospheric compression triggers chorus or increases its intensity [ Gail and Inan , 1990; Gail et al , 1990; Salvati et al , 2000; Fu et al , 2012]. This type of dayside chorus is attributed to compression‐related adiabatic heating leading to electron anisotropy and thus increases in the chorus wave growth rate.…”
Section: Introductionmentioning
confidence: 99%